Analisis Kesalahan Pelafalan Pada Anak Usia Dini dalam Lagu “Burung Kakatua” - Raya Jayana Putri; Azka Ilham Najan; Nanik Khoiroh; Husain Abdul Fidaa` Fitono, Muhammad; Luthfa Nugraheni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study investigated pronunciation errors in early childhood when singing the song “Burung Kakatua”. The purpose of this study was to identify, classify and analyze phonological errors that occurred based on the theory of generative phonology. The research method used was descriptive qualitative research with data collection techniques in the form of observation and recording, on four children aged 2-5 years. Based on the results of the study, the most common pronunciation errors were phoneme substitution (pronunciation of consonant /r/ to /l/), omission of consonant clusters, and phoneme errors in polysyllabic words. Phonological analysis revealed that these errors were related to the development of the child’s speech organs and the complexity of sounds in the song. This study contributes to our understanding of language acquisition and phonological development in early childhood and provides educational implications for educators and parents who help children acquire correct pronunciation through song media.